Deep in the Weeds: Faculty Participation in a Large Scale Deselection Project. Issue 1 (2nd January 2019) - DeMars, J. Michael; Roll, Ann; Phillips, Kevin
Abstract: In 2014, the Pollak Library at California State University, Fullerton embarked on a project to simultaneously address an outdated collection and to provide more student oriented collaborative space by creating a large-scale deselection plan. The interim University Librarian believed it prudent to offer campus faculty the ability to provide input on the deselection plan and an online application was created to allow faculty to request retention of titles selected for weeding. Feedback from an initial weeding pilot program was instructive and the tool was updated for the following deselection rounds to compel faculty to justify reasons for retaining titles and deter arbitrary requests for retention. While ultimately successful in deselecting 95, 074 titles, future weeding projects will focus on the most invested partners, rather than the entire campus community. This article describes Pollak Library's weeding project and analyzes the results of three years of faculty feedback.